Effectiveness of Modified Traps for Protection Against Fruit Flies on Mango - Susanto, Agus; Sudarjat, Sudarjat; Yulia, Endah; Permana, Agus Dana; Gunawan, Aries; Yudistira, Dwi Harya (Jurnal Biodjati, 2020)
Mango is one of the primary fruit export commodities in Indonesia. The productivity of mango can be increased by controlling the pest population, including fruit flies Bactrocera spp. Various efforts to control the population of fruit flies have been carried out, either by implementing traditional methods or by using synthetic pesticides. However, synthetic pesticides can cause pollution, and therefore we need to control the fruit flies’ population by using the most effective fruit fly trap mode. The study was conducted in the mango yield (monoculture) of Department of Agriculture in Majalengka. The traps in this study were modified Steiner traps with funnels, modified Steiner traps without funnels, bottle traps with funnels, bottle traps without funnels, and modified gypsy moth traps. Each trap was fed with 0.2 ml of Methyl eugenol dripped on a cotton roll and hung in the trap. The results showed that the number of fruit flies caught in each trap every week is significantly different. The highest number of fruit flies caught in each trap every week was achieved by bottle traps without funnels that caught 135 flies, while the lowest number of fruit flies caught was recorded by the gypsy moth traps with 16 flies. The transparent color of the bottles and a large number of holes effectively lured the fruit flies into the bottle traps without funnels.